ASYMMETRIC-SYNTHESIS OF 2-ARYL-TETRAHYDROPYRANS VIA ARENE CHROMIUM TRICARBONYL METHODOLOGY .1. CIS-2-ARYL-4-CHLORO-TETRAHYDROPYRANS - Davies, S; Donohoe, T; Lister, M (1991)
Treatment of acetals derived from ortho substituted benzaldehyde chromium tricarbonyl complexes and methanol with homoallylic alcohol and titanium tetrachloride produces the corresponding (RS,RS,SR,RS)-cis-2-aryl-4-chloro-tetrahydropyran complexes completely diastereoselectively. Thus, by this method, homochiral (R)-(-)-o-anisaldehyde chromium tricarbonyl is converted, after decomplexation, to homochiral (R,S)-(+)-cis-2-o-anisyl-4-chloro-tetrahydropyran. © 1991.